Influence of Prior Advice and Beliefs of Mothers on Infant Sleep Position - Von Kohorn, Isabelle (2010)
OBJECTIVES: To determine the relationship between the advice mothers receive about infant sleep position and the actual position they place their infants in to sleep and to understand modifiers of that relationship, especially beliefs about infant comfort and safety. DESIGN: Cross-sectional, face-to-face interviews. SETTING: Women, Infants, and Children centers in the United States from 2006 to 2008. PARTICIPANTS: A total of 2299 predominantly African American mothers of infants younger than 8 months. MAIN EXPOSURE: Advice received and beliefs about infant sleep position. OUTCOME MEASURE: Usually supine infant sleep position. RESULTS: Advice for exclusively supine infant sleep position from family (OR, 1.6; 95% CI, 1.17–2.17), doctors (OR, 2.28; 95% CI, 1.77–2.93), nurses (OR, 1.46; 95% CI, 1.15–1.84), or the media (OR, 1.54; 95% CI, 1.22–1.95) was associated with usually placing an infant supine to sleep. Additional sources of advice for exclusively supine position significantly increase the odds that an infant will be placed supine. Mothers who believe an infant is comfortable supine are more likely to place their infants on their backs to sleep (OR, 4.05; 95% CI, 2.51–6.53). Mothers who believe an infant will choke on its back are less likely to place their infants supine (OR, 0.36; 95% CI, 0.24–0.54). CONCLUSION: Among predominantly African American mothers, increasing advice for exclusively supine sleep and addressing concerns about infant comfort and choking remain critical to getting more infants on their back to sleep.